2018
DOI: 10.1016/j.biortech.2018.03.053
|View full text |Cite
|
Sign up to set email alerts
|

Specific enrichment of hyperthermophilic electroactive Archaea from deep-sea hydrothermal vent on electrically conductive support

Abstract: While more and more investigations are done to study hyperthermophilic exoelectrogenic communities from environments, none have been performed yet on deep-sea hydrothermal vent. Samples of black smoker chimney from Rainbow site on the Atlantic mid-oceanic ridge have been harvested for enriching exoelectrogens in microbial electrolysis cells under hyperthermophilic (80 °C) condition. Two enrichments were performed in a BioElectrochemical System specially designed: one from direct inoculation of crushed chimney … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…Moreover, Archaeoglobus fulgidus has been recently shown to grow on iron by directly snatching electrons under carbon starvation during the corrosion process 20 . Furthermore, Ferroglobus and Geoglobus species were shown to be exoelectrogens in pure culture in a microbial electrosynthesis cell 12 and have been enriched within a microbial electrolysis cell 11 , 13 . Given these elements, the identified Archaeoglobales species could be, under our electrolithoautotrophic conditions, the first colonizers of the electrode during the first days of growth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Archaeoglobus fulgidus has been recently shown to grow on iron by directly snatching electrons under carbon starvation during the corrosion process 20 . Furthermore, Ferroglobus and Geoglobus species were shown to be exoelectrogens in pure culture in a microbial electrosynthesis cell 12 and have been enriched within a microbial electrolysis cell 11 , 13 . Given these elements, the identified Archaeoglobales species could be, under our electrolithoautotrophic conditions, the first colonizers of the electrode during the first days of growth.…”
Section: Discussionmentioning
confidence: 99%
“…The two main hypotheses are the use of similar direct electron transfer pathway as on the anode 9 , or the use of free cell-derived enzymes, which can interact with electrode surfaces to catalyze the electron transfers 10 . Recent studies have shown the exoelectrogenic ability of some hyperthermophilic microorganisms isolated from deep-sea hydrothermal vents belonging to Archaeoglobales and Thermococcales 11 13 , but no studies have been done on environmental samples potentially harboring electrotrophic communities growing naturally with an electric current as their sole energy source.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, electrochemically active microorganisms can utilize various substrates and have been found living in a wide range of temperatures and pH. For instance, it was found that a hyper‐thermophilic electrochemically active Archaea can work even at 80 °C, [ 22 ] and some BESs also exhibited considerable performance even at low temperature (4 °C). [ 23 ]…”
Section: Introductionmentioning
confidence: 99%
“…Very few studies have reported on the diversity of EAMs from extreme environments. These include, for instance, highly saline 17 19 , extreme acidic 20 and alkaline 21 , extreme low 22 and high temperature 19 , 23 , high temperature and pressure 24 , 25 , and deep subsurface 26 habitats. A combination of some of these extreme conditions also exists in some environments.…”
Section: Introductionmentioning
confidence: 99%